Evaluating the Impacts of Procedural and Patient-Specific Factors on the Outcomes of Transcatheter Aortic Valve Implantation (TAVI) - Abilkhair Kurmanaliyev; Rima Braukylienė; Ali Aldujeli; Rassul Zhumagaliyev; Serik Aitaliyev; Ramunas Unikas (Medicina)
Background: Transcatheter aortic valve implantation (TAVI) has emerged as a pivotal intervention for managing severe aortic stenosis in high-risk surgical patients. Objective: This study aimed to evaluate the impacts of procedural factors and patient characteristics on TAVI outcomes, with a focus on survival rates, cardiac mortality, and associated complications. Methods: A retrospective, single-center study involving 224 patients who underwent TAVI at the Lithuanian University of Health Sciences from September 2021 to April 2023 was conducted. Data encompassing demographic characteristics, medical history, procedural specifics, and follow-up outcomes were analyzed. Survival and adverse events were assessed at 30 days, 6 months, and 12 months post-TAVI. Results: The study included 224 patients. The mean age in the non-death group was 80 ± 6.17 years (range, 49–91), while that in the cardiac death group was 81.5 ± 6.14 years (range, 70–94; p = 0.079). Males accounted for 37.7% of the non-death group and 50% of the cardiac death group (p = 0.304). Statistical analyses identified factors significantly associated with mortality and complications. The overall survival rate was 88.8%, with cardiac-related mortality observed in 8% of patients. Increased fluoroscopy time (p < 0.001), a higher contrast volume (p = 0.005), and less improvement in aortic valve velocity post-TAVI (p = 0.031) were significantly associated with cardiac mortality. Advanced age and a reduced left ventricular ejection fraction (<50%) were prominent predictors of adverse outcomes. Patients with non-coronary cusp calcification exhibited lower cardiac mortality (p = 0.005), while mitral valve regurgitation was linked to poorer outcomes (p = 0.015). Logistic regression analysis underscored the incremental risks posed by procedural complexities and comorbidities. Conclusions: Procedural factors such as fluoroscopy duration and contrast volume, along with patient-specific attributes including age, left ventricular function, and valve calcification patterns, critically influence TAVI outcomes. These findings emphasize the need for tailored procedural strategies and patient management protocols to mitigate risks and enhance the efficacy of TAVI interventions.